E-Finance Transformation: A Study of M-Wallet Adoption in Indonesia - Eskasari Putri; Aflit Nuryulia Praswati; Nalal Muna; Nelly Purnama Sari (Muhammadiyah University Press, 2022)
In the era of industry 4.0, the advancement of financial technology has become one of competitive advantage for business. Small, mediun enterprises (SMEs) are encouraged to adopt certain information technology to increase productivity. Financial technology is one of prominent technology that has been widely adopted by SMEs. Specifically, m-wallet payment that promotes cashless society and improve transaction quality. The adoption of financial technology indicate the acceptance of reconfiguring financial management practices in business.Thus, e-financial transformation attempt to digitalize business operations and marketing. This research aims to examine the impact of perceived value, business pressure and technology infrastructure for e-financial transformation and SME’s performance. This is quantitative approach that uses field-survey questionnaire in Surakarta regency. The sampe is 150 owners of SME who have adopted m-wallet payment for transaction at minimum of 1 year. The result shows that perceived value, and technology infrastructure have significant impact on e-financial transformation. However, business pressure and e-financial transformation have no impact on SME’s performance.